Climate-Smart Agriculture in Niger - International Center for Tropical Agriculture; International Crops Research Institute for the Semi-Arid Tropics; United States Agency for International Development (2020)
This Niger country Climate-Smart Agriculture profile provides a snapshot of a developing baseline created to initiate discussion, both within countries and globally, about entry points for investing in CSA at scale